Les zoonoses - Vourc'h, Gwenaël (éditions Quae, 2021)
We have multiple contacts with animals. They are everywhere around us. We share the same environment, the same planet ... and we also share infectious or parasitic diseases. This book sheds a synthetic light on the diseases transmissible between humans and animals, called zoonoses. After having clearly defined what these diseases are, how they are transmitted and presented the major zoonoses, the authors explain the various means of protecting us from them and explain the reasons for their emergence and their evolution. This book invites us to better understand the animal and microbial world that surrounds us. It allows us to understand these diseases in order to better protect ourselves from them and, beyond that, to reconsider the links we have with animals and the entire living world in order to fully reintegrate it.